Konzepte historischen Denkens und ihre Entwicklungslogik: Eine Studie zur Genese historischer Verständnishorizonte - Ammerer, Heinrich (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
This volume investigates the psychogenesis of central historical thinking concepts during the entire schooling phase, describes age-typical characteristics, and attempts to derive generalizable developmental patterns from them. To this end, it begins by reviewing the discourse on conceptual change and the empirical evidence on the genesis of historical consciousness, proposes a three-stage conceptual model, and, on this basis, presents an empirical study in which 100 research partners from kindergarten to adulthood were questioned in partially standardized interviews about their historical ideas, interests, and other flanking aspects of historical consciousness. The results were subjected to a complex statistical data analysis.